Performance analysis of MVDR algorithm in the presence of amplitude and phase errors. - Weimin Su (IEEE Transactions on antennas and propagation)
The sensitivity of spectrum estimation approach, the minimum variance distortionless response (MVDR) spectrum estimator, to random perturbations in the amplitude and phase of array sensors is studied. Analytical expressions for the mean and variance of the spatial spectrum are derived. The effects of the amplitude error on the spectrum is greater relatively than that of the phase error. Theoretical results are validated by the computer simulation. These expressions are then used to study the characteristics of the estimator